A Step Towards a General Framework for Consequential Life Cycle Assessment. (4th April 2016) - Rajagopal, Deepak
Summary: At the core of consequential life cycle assessment (CLCA) is a model of the economic system of which the activity that motivates the CLCA is a part. While there are several applications of CLCA in the literature, there does not appear to exist a formal, general mathematical framework. To address this gap, this article presents a general multi‐market equilibrium framework, which could be adapted to an arbitrary level of complexity depending on the context and data availability. A general expression for total pollution (of a given type) is derived, which highlights different factors that determine the impact on emissions. It is then illustrated how microeconomic theory can help predict the direction of price and quantity changes for each commodity within the modeled system simply based on an activity's relationship to the ultimate activity or service, which motivates the CLCA. The steps involved in converting the multi‐market framework to general equilibrium are also discussed.